Determinants of Underemployment in Ecuador. Period 2019 - Carlosama, Erika (2021)
At the national level, in 2019, people had an inappropriate job - equivalent to 56.7% of the Economically Active Population (EAP) -, of which 1,440,983 people were underemployed - that is, 17.8% of the EAP . Compared to 2018, these figures increased by 158,537 people regarding inappropriate employment and 117,259 regarding underemployment. Thus, the data reflect that the number of people who were not satisfied with their employment increased, either because they received an income below the minimum wage or worked less than the legal day, which has an impact on quality of life and social stability, also showing evidence the inability of the labor market to offer adequate employment. This study proposes to identify the sociodemographic and socioeconomic factors that influence the probability that an Ecuadorian person is underemployed, either by time or by income. To this end, three logistic models (logit) are estimated using data from the National Survey of Employment, Unemployment and Underemployment (ENEMDU) of December 2019. The results obtained suggest that, in general, being a man, residing in an urban area and Contributing to social security are factors that reduce the probability of being underemployed.